Equilibration dynamics and conductivity of warm dense hydrogen - Zastrau, U; Sperling, P; Becker, A; Bornath, T; Bredow, R; Doeppner, T; Dziarzhytski, S; Fennel, T; Fletcher, L; Forster, E; Fortmann, C; Glenzer, S; et al. (American Physical Society, 2014)
We investigate subpicosecond dynamics of warm dense hydrogen at the XUV free-electron laser facility (FLASH) at DESY (Hamburg). Ultrafast impulsive electron heating is initiated by a â‰300-fs short x-ray burst of 92-eV photon energy. A second pulse probes the sample via x-ray scattering at jitter-free variable time delay. We show that the initial molecular structure dissociates within (0.9±0.2) ps, allowing us to infer the energy transfer rate between electrons and ions. We evaluate Saha and Thomas-Fermi ionization models in radiation hydrodynamics simulations, predicting plasma parameters that are subsequently used to calculate the static structure factor. A conductivity model for partially ionized plasma is validated by two-temperature density-functional theory coupled to molecular dynamic simulations and agrees with the experimental data. Our results provide important insights and the needed experimental data on transport properties of dense plasmas. © 2014 American Physical Society.